Impact of Lymphadenectomy on Outcomes of Early-Stage Ovarian Cancer: A Systematic Review and Meta-Analysis - Yao, Guorong; Jin, Xiaotian (Frontiers in Surgery, 2021)
Objective: The study aimed to assess if additional lymphadenectomy with primary staging surgery improves overall survival (OS) and disease-free survival (DFS) of early-stage ovarian cancer (ESOC). Methods: PubMed and Embase databases were searched for any type of study comparing OS or DFS between lymphadenectomy and control groups for any type of ESOC. Adjusted hazard ratios (HR) were pooled in a random-effects model. Results: Twelve studies were included. Meta-analysis indicated that lymphadenectomy is associated with significantly improved OS only for epithelial tumors (HR 0.75 95% CI 0.68, 0.82 I2 = 0% p < 0.00001) but not for malignant germ cell tumors (HR 1.31 95% CI 0.88, 1.94 I2 = 0% p = 0.18). Single studies indicated a tendency of improved OS with lymphadenectomy which was significant for ovarian carcinosarcoma but not for sex cord-stromal tumors. On meta-regression of all histological types, the percentage of patients with lymph node metastasis in the lymphadenectomy group was not found to influence the effect size. Meta-analysis also indicated that lymphadenectomy is associated with significantly improved DFS for epithelial tumors (HR 0.59 95% CI 0.45, 0.77 I2 = 0% p < 0.0001). Single studies on malignant germ cell and sex cord-stromal tumors failed to demonstrate any significant beneficial effect of lymphadenectomy on DFS. Conclusions: Within the limitations of the review, lymphadenectomy may improve OS and DFS for epithelial ESOC. Scarce data suggest that lymphadenectomy is not associated with improved outcomes for malignant germ cell and sex cord-stromal tumors but may benefit ovarian carcinosarcoma. Large-scale RCTs and robust observational studies shall improve current evidence.